Persistence of Chemotherapy-Induced Peripheral Neuropathy Despite Vincristine Reduction in Childhood B-Acute Lymphoblastic Leukemia. (12th May 2022) - Rodwin, Rozalyn L; Kairalla, John A; Hibbitts, Emily; Devidas, Meenakshi; Whitley, Moira K; Mohrmann, Caroline E; Schore, Reuven J; Raetz, Elizabeth; Winick, Naomi J; Hunger, Stephen P; Loh, Mignon L; Hockenberry, Marilyn J; et al.
Abstract: Background: Children with B-acute lymphoblastic leukemia (B-ALL) are at risk for chemotherapy-induced peripheral neuropathy (CIPN). Children's Oncology Group AALL0932 randomized reduction in vincristine and dexamethasone (every 4 weeks vs 12 weeks during maintenance in the average-risk subset of National Cancer Institute standard-B-ALL (SR AR B-ALL). We longitudinally measured CIPN, overall and by treatment group. Methods: AALL0932 standard-B-ALL patients aged 3 years and older were evaluated at T1-T4 (end consolidation, maintenance month 1, maintenance month 18, 12 months posttherapy). Physical and occupational therapists (PT/OT) measured motor CIPN (hand and ankle strength, dorsiflexion and plantarflexion range of motion), sensory CIPN (finger and toe vibration and touch), function (dexterity [Purdue Pegboard], and walking efficiency [Six-Minute Walk]). Proxy-reported function (Pediatric Outcome Data Collection Instrument) and quality of life (Pediatric Quality of Life Inventory) were assessed. Age- and sex-matched z scores and proportion impaired were measured longitudinally and compared between groups. Results: Consent and data were obtained from 150 participants (mean age = 5.1 years [SD = 1.7], 48.7% female). Among participants with completed evaluations, 81.8% had CIPN at T1 (74.5% motor, 34.1% sensory). When examining severity of PT/OT outcomes, only handgrip strength ( P  < .001) and walking efficiency ( P  = .02) improved from T1-T4, and only dorsiflexion range of motion (46.7% vs 14.7%; P  = .008) and handgrip strength (22.2% vs 37.1%; P  = .03) differed in vincristine and dexamethasone every 4 weeks vs vincristine and dexamethasone 12 weeks at T4. Proxy-reported outcomes improved from T1 to T4 ( P  < .001), and most did not differ between groups. Conclusions: CIPN is prevalent early in B-ALL therapy and persists at least 12 months posttherapy. Most outcomes did not differ between treatment groups despite reduction in vincristine frequency. Children with B-ALL should be monitored for CIPN, even with reduced vincristine frequency.